2015
DOI: 10.1891/1946-6560.6.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Harm Reduction Approach to Substance Use in an Intimate Partner Violence Agency: Practice Issues in an Irish Setting

Abstract: There has been growing recognition of the co-occurrence of substance use and intimate partner violence (IPV) victimization in women’s and men’s lives, yet many IPV service providers have not developed an integrated response to these issues. Fewer still have implemented substance use services from a harm reduction approach. This article outlines the approach, policy changes, initial outcomes, and learning points for an IPV agency in Ireland, which implemented a harm reduction response to female IPV survivors wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, their narratives also suggest that practitioners also need to be equipped with information about the support that is available. In Ireland, Morton et al, (2015) demonstrated how training domestic abuse refuge staff about substance use and promoting a harm reduction housing-first approach by changing the refuge policies to include women with substance use, can begin to support women with dual needs. Morton et al, (2015) found that when women with dual needs were welcomed to the refuge, substance use within the refuge did not increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their narratives also suggest that practitioners also need to be equipped with information about the support that is available. In Ireland, Morton et al, (2015) demonstrated how training domestic abuse refuge staff about substance use and promoting a harm reduction housing-first approach by changing the refuge policies to include women with substance use, can begin to support women with dual needs. Morton et al, (2015) found that when women with dual needs were welcomed to the refuge, substance use within the refuge did not increase.…”
Section: Discussionmentioning
confidence: 99%
“…In Ireland, Morton et al, (2015) demonstrated how training domestic abuse refuge staff about substance use and promoting a harm reduction housing-first approach by changing the refuge policies to include women with substance use, can begin to support women with dual needs. Morton et al, (2015) found that when women with dual needs were welcomed to the refuge, substance use within the refuge did not increase. The researchers believed that the stability or reduction of substance use among the women was associated with the '…rigorous attention paid to drafting and implementing a substance use policy in the organization, which gave clear guidelines for responding to a large variety of scenarios that might arise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Established 25 years ago in a large town in Ireland, the organization provides emergency accommodation, keyworker support, counseling, helpline support, children's interventions and court accompaniment. Over the past decade, the organization has developed specific supports and responses to women who are experiencing problematic substance use, and currently; accommodate women within refuge with substance misuse issues; routinely enquire about substance use issues; support women to access substance use stabilization, treatment, and recovery services; provide harm reduction interventions; and provide substance misuse in-reach for residents ( 38 ). In addition, substance misuse responses and interventions are integrated into other services such as the Pattern Change groupwork programme, art therapy and advocacy supports ( 2 ).…”
Section: Methodsmentioning
confidence: 99%